Today's public relations an introduction - Heath, Robert L. (Robert Lawrence), 1941-; Coombs, W. Timothy (Thousand Oaks, Calif. ; London : SAGE, 2006)
'Today's Public Relations' works to redefine the teaching of public relations by discussing its connection to mass communication, but also linking it to its rhetorical heritage.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Public relations